2002
DOI: 10.1007/s004150200031
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of Behçet's disease in a Caribbean population: clinical and imaging findings

Abstract: Behçet's disease (BD) is a chronic relapsing multisystem disorder. While most frequently occurring around the Mediterranean and in Japan, isolated cases of BD have been reported in Africa south of the Sahara and in the Caribbean. The aim of this study was to describe our experience of BD in Guadeloupe (French West Indies) where the presence of the disease has not been reported previously. We analysed retrospectively the charts, and clinical and imaging features of patients native to Guadeloupe who were diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…[2,9,[11][12][13][14][15][16][17]20,30,[34][35][36][37][38][39][40] Moreover, warfarin and acetyl salicylic acid have been given to some CVT patients with BD. [10][11][12]17,26,34 Wechsler et al 14 reported that treatment of CVT during acute phase consisted of combined heparin and steroids in 19 patients, steroids alone in three, and heparin alone in three others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,9,[11][12][13][14][15][16][17]20,30,[34][35][36][37][38][39][40] Moreover, warfarin and acetyl salicylic acid have been given to some CVT patients with BD. [10][11][12]17,26,34 Wechsler et al 14 reported that treatment of CVT during acute phase consisted of combined heparin and steroids in 19 patients, steroids alone in three, and heparin alone in three others.…”
Section: Resultsmentioning
confidence: 99%
“…35 Colchium, prednisolone, azathioprine, cyclosporine, and cyclophosphamide have been administered to prevent the recurrence of CVT in BD. 2,9,15,17,[26][27][28]30,[36][37][38][39][40][41][42] Acetazolamide and lumboperitoneal shunts have been installed to reduce intracranial hypertension in some CVT patients with BD. 20,25 We administered colchium, azathioprine, and/or prednisolone to our patients to prevent recurrence and we have not observed any recurrence during follow-up in CVT patients with BD.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 7 patients the myelitis was partial in 3, transverse in 2, and presented as a Brown-Séqard syndrome in 2. In addition to this series a number of case reports describe myelopathic involvement in Behçet's disease (Morrissey et al, 1993a;Yoshioka et al, 1996;Mascalchi et al, 1998;Kocer et al, 1999;Green and Mitchell, 2000;Harmouche et al, 2000;Lee et al, 2001;Lannuzel et al, 2002;Moskau et al, 2003;Calguneri et al, 2005;Deshpande et al, 2005;Mullins et al, 2009;Fukae et al, 2010;Metreau-Vastel et al, 2010). Behçet's associated myelitis is typically longitudinally extensive and extension of upper cervical cord lesions into brainstem structures can occur.…”
Section: Behçet's Diseasementioning
confidence: 90%
“…In most NBD patients with myelitis, highdose systemic corticosteroid therapy was reported to be effective for the acute or subacute phase (1,(11)(12)(13)19). However, there were some reports describing patients who showed a poor response to corticosteroid ther-apy (5,10,13,16,17). In those patients, other immunosuppressants or interferon α may be used (1,10,17 …”
Section: T a B L E 1 Cl I N I C A L Co U R S E O F Ne U R O -B E H mentioning
confidence: 99%